Stability Control and Quick Retaining Technology of Gob-Side Entry: A Case Study - Hengjie Luan; Yujing Jiang; Lujie Zhou; Huili Lin (Advances in Civil Engineering)
In Chinese coal mines, gob-side entry retaining, an efficient technique for coal mining, has been widely used. However, severe roadway deformation and slow retaining speed have gravely restricted the popularization and its application. Hence, in order to solve the existing problems, the deformation mechanism of gob-side entry was studied. Then, a new approach for gob-side entry retaining technique (GERT) was proposed to increase the speed of gob-side entry retaining. Finally, the application effect of the new GERT method was tested and analysed. The results show that the rotation and subsidence of roof key block B lead to severe deformation of roadway. And the proposed gob-side entry stability control technology can affectively resist the severe roadway deformation. Compared with the conventional support method for gob-side entry retaining, GERT has completed the complex wall construction work in advance, thereby simplifying the process of gob-side entry retaining and increasing the speed of gob-side entry retaining. When retaining the entry in panel 183U04 with the new support method, the entry retaining speed significantly improved from 0.25 m/h to 1.0 m/h compared with the traditional method, and then the problem of gob-side entry severe deformation was solved.